Thermodynamic Bebavior of Scroll Compressor with Economizer for Heat Pump - 马国远; 彦启森 (Zhileng xuebao)
The heat pump cycle employing scroll compressor with an economizer was developed and its characteristics were thermodynamically analyzed. The results show that the cycle can remarkably improve the adaptability of heat pump to low ambient temperature environment. The economizer pressure is optimized by analyzing its influences on the performances of the heat pump.